(3GSgGeGJ GdHMK GdJQHhj aj HYV GdHdOGf GdYQHjI aj eLGd GdJYdje GdhLOGfj hEMOGK GdJZjQ GdGLJeGYj(B: (3OQGSI ejOGfjI dYjfI eNJGQI ef GdHMhK hGdOQGSGJ GdJQHhjIs - (3GdehShj, fGUQs ((3HjQhJs (3GdgjFI GddHfGfjI ddYdhe GdJQHhjIs, 2006)
(3jOhQ GdHMK GdMGdj Mhd eOi ESgGe GdHMK GdJQHhj aj KdGK Ohd YQHjI (B((3GdHMQjf, heUQ, hGdchjJ(B) (3aj eLGd GdJYqde GdhLOGfj hEMOGK GdJZqjQ GdGLJeGYj aj eLJeYGJfG GdYQHjI(B. (3hJe JfGhd gPG GdESgGe ef NdGd GdQLhY Edi YjfI eNJGQI ef GdHMhK hGdOQGSGJ GdJQHhjI aj GdOhd GdKdGK HdZ eLehYgG (B(354) (3HMKkG hOQGSI, hPdc ef CLd JYqQa(B: 1) (3eOi GgJeGe gPg GdHMhK hGdOQGSGJ HGdJYqde GdhLOGfj aj YdGbJg HGdJZqjQ GdGLJeGYj hEMOGKg; (B2) (3hGdUhQI GdJj JXgQgG dCKQ GdJYdje aj eLGd GdJYqde GdhLOGfj ddWdHI aj eOGQSfG; (B3) (3hGdOhQ GdPj Jbhe Hg aj GdeSGYOI Ydi Jchjf efXheI bjejI dOi GdWdGH JSge aj EMOGK GdJZqjQ GdGLJeGYj aj eLJeYGJfG GdYQHjI(B. (3hbO GSJYed GdHMK GdefgL GdhUaj GdJMdjdj aj JfGhdg dehVhYGJg, MjK bGe HhUa GdHjGfGJ GdeJhGaQI hJMdjdgG(B. (3hhqXa JMdjd GdeMJhi CSdhHkG dPdc eYJeOkG GdacQI (Btheme (3hMOI dgPG GdJMdjd(B. (3CeG COhGJ GdHMK, agj eLehYI ef GdHMhK hGdOQGSGJ GdJQHhjI GdYQHjI GdJj CLQjJ Vef eLGd ehVhYGJg aj GdOhd GdKdGK(B. (3hbO GSJYedJ gPg GdeLehYI YjfI ddHMK(B. (3CeG CHQR GdfJGFL GdJj JhUd ZdjgG GdHMK GdMGdj agj(B: - (3Ydi GdQZe ef GgJeGe GdHMhK hGdOQGSGJ YjfI GdHMK HGdJYqde GdhLOGfj hGdJZqjQ GdGLJeGYj, EdqG Cf gPG GdGgJeGe bO LGA YGekG hZjQ eMOO, abO hQO Vef JfGhd CehQ hbVGjG YGeI heJYOOI NGUI HGdefgL GdeOQSj;s
(3GdfhY (B: (3aUd aj cJGHs
Keywords: Arab Countries; Educational Research Social Change; Pays Arabes; Recherche en Education Changement Social; (3GdHMK GdJQHhj GdJZjQ GdGLJeGYjs; (3GdOhd GdYQHjIs